Clinical Value of 3‐Dimensional Ultrasound in Gynecology. (2nd March 2018) - Levine, Elliot M.; Fernandez, Carlos M.; Miller, Daniel; Locher, Stephen
Abstract : This report provides examples of using 3‐dimensional ultrasound diagnostically in gynecology. The cost efficiency it provides and the wide range of applications it has support the routine use of this ultrasound technology in the practice of gynecology.